NRAS destines tumor cells to the lungs - Anastasios D Giannou; Antonia Marazioti; Nikolaos I Kanellakis; Ioanna Giopanou; Ioannis Lilis; Dimitra E Zazara; Giannoula Ntaliarda; Danai Kati; Vasileios Armenis; Georgia A Giotopoulou; Anthi C Krontira; Marina Lianou; et al. (EMBO Molecular Medicine)
Abstract The lungs are frequently affected by cancer metastasis. Although NRAS mutations have been associated with metastatic potential, their exact role in lung homing is incompletely understood. We cross‐examined the genotype of various tumor cells with their ability for automatic pulmonary dissemination, modulated NRAS expression using RNA interference and NRAS overexpression, identified NRAS signaling partners by microarray, and validated them using Cxcr1‐ and Cxcr2‐deficient mice. Mouse models of spontaneous lung metastasis revealed that mutant or overexpressed NRAS promotes lung colonization by regulating interleukin‐8‐related chemokine expression, thereby initiating interactions between tumor cells, the pulmonary vasculature, and myeloid cells. Our results support a model where NRAS‐mutant, chemokine‐expressing circulating tumor cells target the CXCR1‐expressing lung vasculature and recruit CXCR2‐expressing myeloid cells to initiate metastasis. We further describe a clinically relevant approach to prevent NRAS‐driven pulmonary metastasis by inhibiting chemokine signaling. In conclusion, NRAS promotes the colonization of the lungs by various tumor types in mouse models. IL‐8‐related chemokines, NRAS signaling partners in this process, may constitute an important therapeutic target against pulmonary involvement by cancers of other organs.